2021
DOI: 10.1021/acs.jpcc.1c05139
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Anisotropic Thermomechanical Response to Shock Wave Loading in Oriented Samples of the Triclinic Molecular Crystal 1,3,5-Triamino-2,4,6-trinitrobenzene

Abstract: All-atom molecular dynamics (MD) simulations were used to study shock wave loading in oriented single crystals of the highly anisotropic triclinic molecular crystal 1,3,5-triamino-2,4,6-trinitrobenzene (TATB). The crystal structure consists of planar hydrogen-bonded sheets of individually planar TATB molecules that stack into graphitic-like layers. Shocks were studied for seven systematically prepared crystal orientations with limiting cases that correspond to shock propagation exactly perpendicular and exactl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 111 publications
2
20
0
Order By: Relevance
“…Recent work from Lafourcade et al showed a strong orientation dependence for deformation mechanisms in TATB under controlled strain conditions 55 that leads to analogous deformations under shock conditions. 56 For instance, compressive stresses along [100] result in an inelastic chevron-like buckling of the basal planes, whereas resolved shear stresses along (011)-type planes result in a nonbasal gliding of the planes. Under weak stresses, the TATB crystal layers will glide in-plane 55,57,58 while detonation-level shocks lead to the formation of nanoscale shear bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work from Lafourcade et al showed a strong orientation dependence for deformation mechanisms in TATB under controlled strain conditions 55 that leads to analogous deformations under shock conditions. 56 For instance, compressive stresses along [100] result in an inelastic chevron-like buckling of the basal planes, whereas resolved shear stresses along (011)-type planes result in a nonbasal gliding of the planes. Under weak stresses, the TATB crystal layers will glide in-plane 55,57,58 while detonation-level shocks lead to the formation of nanoscale shear bands.…”
Section: Introductionmentioning
confidence: 99%
“…All-atom simulations were used to study the perfect crystal shock response in a variety of crystallographic orientations. 56 This showed significant effects on the wave structure (single vs two-wave response), elastic wave speeds, and deformation mechanisms, which ranged from a variety of crystal-level defect formations to plasticity and intense shear localization. Coupled MD and continuum simulations explored the mechanics of pore collapse for various orientations and shock speeds for cylindrical pores.…”
Section: Introductionmentioning
confidence: 99%
“…The wavefront does not reach a clean, nearly planar shape until it reaches the closely packed central region of our sample (40–60 ps). At this point, a two wave (elastic‐plastic) shock structure can be seen, with plastic particle velocities mostly independent of the grain despite high levels of anisotropy in TATB [91]. In the final two frames, when the shock front re‐enters a porous region, molecular jetting into voids accelerates the wave locally, which leads to the bands of higher velocity (red) regions seen in the 80 ps frame.…”
Section: Shock Responsementioning
confidence: 93%
“…Several mechanisms are responsible for the sensitivity which, in addition to dependence on the underlying molecular structures of the ingredients, stems from energy localization at defects and the formation of hotspots [2,3]. Collapse of pre-existing pores in the crystal [4][5][6][7][8], formation of shear bands [9][10][11][12], friction between sliding crystals and other interfaces [13][14][15], and plastic dissipation [16][17][18] are thought to be the most important mechanisms for hotspot formation. Among these, pore collapse and shear bands predominate at high shock intensities.…”
Section: Introductionmentioning
confidence: 99%